Simulation Study of Oxygen Ion irradiation with Aluminum at different energies : A Simulation study. (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The effect of irradiation by energetic ions with substrate modifies the material properties at the surface and core level, for This simulation work oxygen ions with different energies ranging from 5KeV to 25 KeV are considered and irradiated with aluminum material. When oxygen ions with energies 5KeV to 25KeV are bombarded on surface materials, it modifies characteristics of target materials at the surface level and that surface becomes corrosion resistant. In the present work 5KeV to 25KeV energy, Oxygen ions are bombarded on the Aluminum surface, improving a material's corrosion resistance. In the present study, only 5KeV to 25KeV energy oxygen ions are used. SRIM-based simulation is used for high energy Oxygen ions from 5 keV to 25 keV were introduced into Aluminum target material with a depth of 1500 Angstrom. In the present work, 5 KeV - 25 KeV simulated ion beam is used for implantation purposes and the depth of material is taken at about 1500 angstrom and near about profile of about 100000 ions was observed. Surface Binding energy is observed 3.26 eV, while lattice Binding energy is observed 3 eV In this case number of backscattered ions is from 2371 to 857 for energy ranging from 5KeV to 25 KeV, vacancies per ion are observed 47 at 5 keV and increased to 178 at 25 keV, longitudinal range of ions in material is about 135 Angstrom at 5 keV while 552 at 25 keV, similarly radial range of ions is about 81 Angstrom at 5 keV while 280 at 25 keV.